2011
DOI: 10.1016/j.molimm.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Endoribonuclease activities of porcine reproductive and respiratory syndrome virus nsp11 was essential for nsp11 to inhibit IFN-β induction

Abstract: Previous studies have shown that PRRSV nsp11, which was an endoribonuclease, was an interferon antagonist, however, the mechanism that nsp11 inhibited IFN-β production was unclear. To explore whether the endoribonuclease was required for nsp11 to disrupt the IFN-β production, substitutions of the presumed catalytic histidine and lysine residues of nsp11 were introduced into plasmid pcDNA 3.1-FLAG. The results showed that mutation that inactivated endoribonuclease made nsp11 lose its ability to inhibit Poly(I:C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 40 publications
3
61
0
Order By: Relevance
“…2C), suggesting that each MCV protein inhibited an event upstream of IRF3 activation. Nsp11 overexpression also did not inhibit constitutively active IRF3, which was expected given that nsp11 is thought to act as an endoribonuclease to target the degradation of MAVS transcripts (49,50). Viral protein level expression was verified by immunoblotting to ensure that the lack of inhibition was not due to a lack of protein expression.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…2C), suggesting that each MCV protein inhibited an event upstream of IRF3 activation. Nsp11 overexpression also did not inhibit constitutively active IRF3, which was expected given that nsp11 is thought to act as an endoribonuclease to target the degradation of MAVS transcripts (49,50). Viral protein level expression was verified by immunoblotting to ensure that the lack of inhibition was not due to a lack of protein expression.…”
Section: Resultsmentioning
confidence: 96%
“…However, the overexpression of MC159, or any other FLIP, did not induce IFN-β enhancer activity in both cell types tested here. The porcine reproductive and respiratory syndrome virus (PRRSV) nsp11 protein is a known inhibitor of IFN-β activation via its ability to inhibit IRF3 and NF-κB (49,50). As would be expected, luciferase activity was low in nsp11-expressing cells and was used as a positive control.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, despite recent advances in our understanding of PRRSV replicase polyproteins (Li et al, 2014;Liu et al, 2012;Shi et al, 2011;Sun et al, 2012), various aspects of nsps remain unclear. PRRSV nsp7 is the largest subunit in the nsp5-nsp8 region, and is flanked by nsp6 and nsp8.…”
Section: Discussionmentioning
confidence: 99%
“…ORF1a and ORF1b occupy approximately 75% of the viral genome and encode the replicase polyproteins pp1a and pp1ab, respectively, which are cleaved into at least 14 functional nsps by viral protease (den Boon et al, 1995;Fang and Snijder, 2010;Snijder et al, 1994). Recent studies have revealed that PRRSV nsp2 is involved modulating type 1 interferon (IFN) activity (Sun et al, 2012), nsp9 and nsp10 contribute to the fatal virulence of highly-pathogenic PRRSV (Li et al, 2014) plays an important role in IFN inhibition and viral genome synthesis (Shi et al, 2011). Nsp1, nsp2, and nsp7 were shown to induce high levels of antibody responses during PRRSV infection (Brown et al, 2009).…”
Section: Introductionmentioning
confidence: 99%